Repeated loading of fine grained soils for pavement design - Loach, Simon C. (1987)
The primary aim of this research was to investigate the behaviour of a clay subjected to a loading regime similar to that experienced by a road subgrade under traffic loading in Great Britain. The material used was Keuper Marl. The samples were anisotropically consolidated in a triaxial apparatus from a slurry which allowed careful control over the stress history and produced uniform samples. The samples were fully instrumented and the apparatus was capable of applying repeated axial and radial stresses. The test programme was designed to investigate the resilient and permanent response of the samples to a variety of stress pulse magnitudes and time periods.